2023
DOI: 10.3389/fimmu.2023.1244345
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor-guided therapeutic intervention of human cancers: molecular and immunological perspectives

Suprabhat Mukherjee,
Ritwik Patra,
Payam Behzadi
et al.

Abstract: Toll-like receptors (TLRs) serve as the body’s first line of defense, recognizing both pathogen-expressed molecules and host-derived molecules released from damaged or dying cells. The wide distribution of different cell types, ranging from epithelial to immune cells, highlights the crucial roles of TLRs in linking innate and adaptive immunity. Upon stimulation, TLRs binding mediates the expression of several adapter proteins and downstream kinases, that lead to the induction of several other signaling molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 344 publications
0
30
0
Order By: Relevance
“…In this study, we examined functional roles of PTK2 in lung cancer progression via the cross-talk between EGFR-and TLRs-mediated signaling, which has been considered as critical therapeutic targets for the intervention of lung cancer diseases [3][4][5][6][7][8][9]. We found that the survival of NSCLC patients with up-regulated PTK2 was critically lower than that of TLRs-mediated signaling is essentially implicated in lung cancer progression [3][4][5][6][7][8][9][10][11][12], the ability of cancer progression was significantly enhanced in response to EGF, Pam3csk4 (an agonist of TLR1/2), and FSL-1…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we examined functional roles of PTK2 in lung cancer progression via the cross-talk between EGFR-and TLRs-mediated signaling, which has been considered as critical therapeutic targets for the intervention of lung cancer diseases [3][4][5][6][7][8][9]. We found that the survival of NSCLC patients with up-regulated PTK2 was critically lower than that of TLRs-mediated signaling is essentially implicated in lung cancer progression [3][4][5][6][7][8][9][10][11][12], the ability of cancer progression was significantly enhanced in response to EGF, Pam3csk4 (an agonist of TLR1/2), and FSL-1…”
Section: Discussionmentioning
confidence: 99%
“…With advanced omics data analysis of lung cancer patients, numerous genetic and molecular studies have been reported for pathophysiological characterization of lung cancer progression and the development of target-therapeutics [3][4][5]. Recently, the development of therapeutic targets focusing on toll-like receptors (TLRs) and epidermal growth factor receptor (EGFR) signaling is being potentially considered in lung cancers [6][7][8][9]. TLRs have been identified on tumor cells, where their activation may orchestrate downstream signaling pathways that serve crucial functions in tumorigenesis and tumor progression [6,7,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, accumulating studies indicated inflammation are closely related to the progression of CHD 1,2 . Interleukins (ILs) are inflammatory cytokines involved in pro‐inflammatory and anti‐inflammatory responses through interactions with a variety of receptors, such as Toll‐like receptors (TLRs) 3 . Research has suggested that ILs and TLRs could represent promising targets for the therapeutic intervention of inflammation‐associated diseases 4 .…”
Section: Introductionmentioning
confidence: 99%
“…reviewed the TLR proteins and the therapeutic strategies against cancers. [17] A chemical compound that has pharmacological or biological activity that is likely to be therapeutically useful but may still have a sub-optimal structure that needs to be modified to fit better to the target is called a lead compound in the drug discovery process. Lead compounds offer the possibility of being followed by backup compounds.…”
Section: Introductionmentioning
confidence: 99%